An Enhanced Electronic Health Community With Knowledge-Based E-Mail And Agent-Based Knowledge Search And Sharing. - Cheah, Yu N; Abdul Rashid, Faridah (2004)
Electronic health communities have the potential to go beyond providing basic communication-type services such as online chat and discussion group, health directories and specialised portals for healthcare practitioners.